Bias against the null hypothesis: Scaring pregnant women about drugs in pregnancy - Koren, Gideon (College of Family Physicians of Canada, 2014)
Question Since the thalidomide disaster, medicine is practised as if every drug is teratogenic, when in fact very few medications are. Pregnant women are often ready to refuse treatment even for life-threatening conditions owing to misinformation and misperceptions about fetal risks. How can I reassure my patients and prevent misinformation from affecting their treatment? Answer Physicians must provide evidence-based counseling to their patients. For example, antihistamines for morning sickness have been proven safe in numerous studies, but are commonly the subject of media reports overstating the risks to the fetus. Family physicians and obstetricians must take an active role in preventing pregnant patients from being misinformed.